Joanna Bator w polskim polu literackim - Kocznur, Agnieszka (Przestrzenie Teorii, 2021)
The starting point of the article is locating Joanna Bator in the Polish literary field using Pierre Bourdieu’s methodology, and considering such elements as gender determinants, the author’s attitude towards the media and self-creation, and the time of the prose’s debut. The Nike Prize Bator was awarded in 2013, and not only did enable this author to maintain autonomy in her field, but also led to a change in poetics, i.e. a change in the dominant genre of her novel from magical realism to fairy tale. The article describes the conditions that influenced the transfer of the author by critics from the current of high and award-winning literature to the prose of the medium.